2018
DOI: 10.1038/s41467-018-03062-w
|View full text |Cite
|
Sign up to set email alerts
|

A dual mechanism promotes switching of the Stormorken STIM1 R304W mutant into the activated state

Abstract: STIM1 and Orai1 are key components of the Ca2+-release activated Ca2+ (CRAC) current. Orai1, which represents the subunit forming the CRAC channel complex, is activated by the ER resident Ca2+ sensor STIM1. The genetically inherited Stormorken syndrome disease has been associated with the STIM1 single point R304W mutant. The resulting constitutive activation of Orai1 mainly involves the CRAC-activating domain CAD/SOAR of STIM1, the exposure of which is regulated by the molecular interplay between three cytosol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
75
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(85 citation statements)
references
References 44 publications
9
75
0
1
Order By: Relevance
“…The substitution of R304 by tryptophan (p.R304W), and to lesser extent by glutamine (p.R304Q), increases the local hydrophobicity and α‐helical rigidity, and leads to the conformational change of the second and third CC1 α‐helix. This compromises the maintenance of the CC1–CC3 clamp, ultimately destabilizes the tight conformation of STIM1, promotes the exposure of the SOAR domain, and enhances the CC1–CC1 homodimerization and the activation of ORAI1 independently of the reticular Ca 2+ load (Fahrner et al, ).…”
Section: Stim1 and Orai1 Mutationsmentioning
confidence: 99%
“…The substitution of R304 by tryptophan (p.R304W), and to lesser extent by glutamine (p.R304Q), increases the local hydrophobicity and α‐helical rigidity, and leads to the conformational change of the second and third CC1 α‐helix. This compromises the maintenance of the CC1–CC3 clamp, ultimately destabilizes the tight conformation of STIM1, promotes the exposure of the SOAR domain, and enhances the CC1–CC1 homodimerization and the activation of ORAI1 independently of the reticular Ca 2+ load (Fahrner et al, ).…”
Section: Stim1 and Orai1 Mutationsmentioning
confidence: 99%
“…Briefly, mutations of STIM1 mostly reside in the EF-hand Ca 2+ -binding motifs, most likely modifying the affinity for Ca 2+ ions of the protein, with few exceptions located on the cytosolic coiled-coil domains. The R304W mutation has recently been shown to affect the dimerization and resting state of STIM1 (Fahrner et al, 2018). A second substitution at the same position (R304Q; Harris et al, 2015) and a deletion on the third coiled-coil domain have also been reported (I484R fs*21; Okuma et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The luminal R304W mutation does not interfere with Ca 2+ binding. Instead, a recent study revealed that it induces a helical elongation within the coiled-coil domain, and thereby promotes STIM1 clustering and the exposure of the SOAR domain (37). In both cases, the mutations induce constitutive ORAI1 binding and activation, resulting in major extracellular Ca 2+ influx despite replete Ca 2+ stores (4, 1012).…”
Section: Discussionmentioning
confidence: 99%